Analisis Perumusan Strategi Bisnis Pada Usaha Fesyen - Adiwangsa, Adiwangsa; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The rapid growth of business in the fashion sector in Indonesia makes fashion business competition in Indonesia very tight. To be able to survive in the tight business competition in the fashion sector, Convoa Jakarta, a business engaged in the fashion industry, has a number of problems caused by the lack of planning and strategic management at Convoa Jakarta. This condition is the background of this research, with the aim of identifying internal and external factors of Convoa Jakarta, conducting analysis using strategy formulation to produce appropriate strategic decisions for Convoa Jakarta's business development. This study uses a descriptive qualitative approach with primary data sources in the form of primary data from interviews, as well as secondary data in the form of company documents and journal articles. The analysis tools used are IFE Matrix, EFE Matrix, SWOT, and QSPM Matrix. The results showed that QSPM Matrix produces business development strategies to increase market share for existing products by carrying out more intense marketing activities. Abstrak Pesatnya pertumbuhan usaha dibidang fashion di Indonesia membuat persaingan usaha fesyen di Indonesia sangat ketat. Untuk dapat bertahan dalam ketatnya persaingan bisnis dibidang fesyen, Convoa Jakarta sebuah usaha yang bergerak dibidang industri fesyen memiliki sejumlah permasalahan yang disebabkan oleh minimnya perencanaan dan manajemen strategi pada Convoa Jakarta. Kondisi tersebut melatarbelakangi dilakukannya penelitian ini, dengan tujuan mengidentifikasi faktor-faktor internal dan eksternal Convoa Jakarta, melakukan analisis menggunakan formulasi strategi hingga menghasilkan keputusan strategi yang tepat guna pengembangan usaha Convoa Jakarta. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan sumber data utama berupa data primer dari wawancara, serta data sekunder berupa dokumen perusahaan dan artikel jurnal. Alat analisis yang digunakan yaitu IFE Matrix, EFE Matrix, SWOT, dan QSPM Matrix. Hasil penelitian menunjukan bahwa QSPM Matrix menghasilkan strategi pengembangan bisnis meningkatkan pangsa pasar untuk produk yang sudah ada dengan melakukan kegiatan pemasaran yang lebih intens.